2018
DOI: 10.7717/peerj.4248
|View full text |Cite
|
Sign up to set email alerts
|

Weekend effect in upper gastrointestinal bleeding: a systematic review and meta-analysis

Abstract: AimTo perform a systematic review and meta-analysis of the weekend effect on the mortality of patients with upper gastrointestinal bleeding(UGIB).MethodsThe review protocol has been registered in the PROSPERO International Prospective Register of Systematic Reviews (registration number: CRD42017073313) and was written according to the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) statement. We conducted a search of the PUBMED, COCHRANE, EMBASE and CINAHL databases from inception t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
21
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(24 citation statements)
references
References 41 publications
(61 reference statements)
1
21
0
2
Order By: Relevance
“…We found that the use of clinical audit data did not necessarily mean that measures of severity were included in the analysis [ 39 ] and that measures of severity inevitably varied. In a systematic review of the effect of weekend admission on outcomes for patients with upper gastrointestinal bleeding, variceal bleeding was not associated with weekend admission, but non-variceal bleeding was, suggesting that a more sophisticated approach than a ‘severity measure’ may be important and may be disease-specific [ 40 ].…”
Section: Discussionmentioning
confidence: 99%
“…We found that the use of clinical audit data did not necessarily mean that measures of severity were included in the analysis [ 39 ] and that measures of severity inevitably varied. In a systematic review of the effect of weekend admission on outcomes for patients with upper gastrointestinal bleeding, variceal bleeding was not associated with weekend admission, but non-variceal bleeding was, suggesting that a more sophisticated approach than a ‘severity measure’ may be important and may be disease-specific [ 40 ].…”
Section: Discussionmentioning
confidence: 99%
“…Although a retrospective study from Japan concluded that the clinical outcomes of patients who underwent emergency endoscopic hemostasis for acute UGIH outside regular hours did not differ from those of patients treated during regular hours [100], two systematic reviews/meta-analyses found otherwise [95,101]. Xia et al reported that NVUGIH patients who were admitted out of hours had significantly higher mortality and received less timely endoscopy [95].…”
Section: On-call Gi Endoscopy Resourcesmentioning
confidence: 99%
“…Xia et al reported that NVUGIH patients who were admitted out of hours had significantly higher mortality and received less timely endoscopy [95]. Shih and colleagues showed that the "weekend effect" was associated with increased mortality in UGIH patients, particularly in patients with NVUGIH [101].…”
Section: On-call Gi Endoscopy Resourcesmentioning
confidence: 99%
“…Hence, in this study we included UGIB patients with variceal and nonvariceal bleeding. The importance of the timing of endoscopy in UGIB is further highlighted by the report of weekend effect, whereby the prognosis of patients presenting after hours may be worse [10,11].…”
Section: Introductionmentioning
confidence: 99%